IMPLEMENTATION OF FOUR BASIC PHYSICAL LAWS IN THE ADVENTURE GAME "ESCAPE LAND" - Mohammad Habibulloh; Agus Sifaunajah (JARES (Journal of Academic Research and Sciences), 2019)
There is no doubt that games are a big part of the technology that is experiencing rapid development. Many people think that games are only entertainment in their spare time, but during the development of technology, games are also included in the category of learning media. Games are often used as simulation media in large companies and developing companies, not only on a company scale but in education they can also use games as an alternative media for limited learning facilities, as well as tools and materials owned by these educational institutions. In this study, the author will try to make a game that functions not only as an entertainment medium but also as learning for all people, especially students in the field of science to improve skills in the field of physics. The game that the author wants to make, elements in the game are not fixated by learning like in class in general, but the author provides a challenge in the game in the form of exciting adventures so that the game players consciously or unconsciously can learn the physics of the science-packed in the game.